Prenatal diagnosis of ornithine carbamoyl transferase deficiency using a gene specific probe. Issue 6 (December 1985) - Pembrey, M E; Old, J M; Leonard, J V; Rodeck, C H; Warren, R; Davies, K E
Abstract : A gene specific DNA probe has been used to predict the genotype of two fetuses in families at risk for ornithine carbamoyl transferase deficiency. Although the probe does not detect the mutation directly, prediction was possible by examining restriction fragment length polymorphisms of the parents and sibs to identify the X chromosome carrying the mutation. It is suggested that in all pregnancies, regardless of the predicted outcome, the biochemical status of carrier mothers should be monitored because hyperammonaemia and arginine deficiency may have a deleterious effect on the fetus.